(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Agustina S, Wiryawan KG, Suharti S, Meryandini A. 2021. The enrichment process and morphological identification of anaerobic fungi isolated from buffalo rumen. Biodiversitas 23: 469-477. Anaerobic fungi are one of the microbes that have an important role in rumen fiber degradation because they can produce cellulase enzymes and penetrate feed particles. Nevertheless, few studies were performed to test the potential of anaerobic fungi in Indonesia. Therefore, the present study was carried out to evaluate the impact of the enrichment process on pH value, the zoospores population, NH3 (ammonia) concentration, and VFA (Volatile Fatty Acid) proportion. In addition, this research was also performed to isolate anaerobic fungi from buffalo rumen and identify their morphological characteristics. The enrichment stage of anaerobic fungi was carried out using the Hungate method. Results showed that the population of fungi zoospores, pH value, ammonia concentration, the proportion of acetate, and total VFA were significantly affected by the incubation time (P<0.01). In addition, Caecomyces, Neocallimastix, and Piromyces were rumen anaerobic fungi isolated from buffalo rumen with different morphological characteristics. It can be concluded that the incubation time increased the zoospore population, the concentration of NH3, acetate proportion, and total VFA but decreased media’s pH value.